Specifying with syntactic theory functors - Haveraaen, Magne; Roggenbach, Markus (Journal of logical and algebraic methods in programming, 2020)
We propose a framework, syntactic theory functors (STFs), for creating syntactic structuring mechanisms for specification languages. Good support for common reuse patterns is important for systematically developing specifications for large systems. Though immaterial to foundational theory, lack of support otherwise causes lengthy writing of boilerplate code or repeated adaptation from one context to another. We present STFs in the context of the Goguen & Burstall institution theory. This theory captures the essential structure of ontologies, modelling and formal specifications (OMS). In particular it provides powerful structuring mechanisms that are independent of the specification formalism, i.e., they are institution-independent. The presented STF framework is institution-independent as well. As such it encompasses many approaches to software and information systems. STFs subsume the standard institution-independent structuring mechanisms, and open up new ways of reusing existing and structuring new specifications. In this, STFs subsume and enrich the tool-set of ‘good practices’, which includes separation of concerns, ease of reuse of specification-text, and improved theorem proving support. STFs are aimed at structuring and reuse beyond the classical mechanisms. However, most STFs are institution-specific and support specific reuse patterns in that institution. With such institution-specific STFs it is possible to incrementally grow more complex institutions from simpler ones. This is very much needed when developing ontologies or specification languages for a new domain. In this paper, we motivate STFs with examples in Casl, the common standard algebraic specification language. We further demonstrate how STFs can ease specification through capturing repeated constructions once and for all as patterns formulated as STFs.